Lost to follow up from chronic care services during COVID-19 from health facilities, in Northwest Ethiopia - Belay, Daniel Gashaneh; Adugna, Asmamaw (Frontiers in Epidemiology, 2022)
Introduction The COVID-19 pandemic and the responses to it have greatly altered individual lives, particularly those with chronic illnesses. The pandemic affected the processes of routine comprehensive care for patients. Because chronic illnesses depress the immune system, they make individuals more susceptible to infection as well as more sickly and less likely to recover from the COVID-19 pandemic. Because of this, the rate of loss to follow-up (LTFU) from chronic illness care is accelerated by the COVID-19 pandemic, and the number of patients receiving new treatments is decreased. Therefore this study aimed to assess the mean difference of loss to follow-up among HIV/AIDS, diabetes mellitus (DM), and hypertension patients during the COVID-19 period as compared to pre-COVID-19 at health facilities in Northwest Ethiopia. Methods An institution-based secondary data analysis of the Gondar city health report from October 2019 to Jun 2021 was done. Excel data were transformed to STATA 14 for analysis. An independent t-test was used to compare the mean difference of loss to follow-up and new initiation of treatment among HIV/AIDS, DM, and hypertension patients during the pre-COVID-19 and COVID-19 periods at facilities in Northwest Ethiopia. Variables with a mean difference of p < 0.005 with a 95% confidence interval were used to declare the significant level. Result There was a significantly higher mean difference in the number of patients with LTFU from Anti-Retroviral Therapy (ART) and antihypertensive treatment during COVID-19 as compared to the pre-COVID-19 period [μd =17.85, 95%CI: 3.25, 32.95] and [μd =17.31, 95%CI: 8.35, 26.97] respectively. The mean number of patients who were newly started anti-hypertensive treatment during the COVID-19 season was significantly decreased as compared to those who were before the COVID-19 period [μd = −32.94, 95%CI: −63.76, −2.12]. Conclusion There was a significantly higher mean difference in the number of patients with LTFU from Anti-Retroviral Therapy (ART) and antihypertensive treatment during COVID-19 as compared to the pre-COVID-19 period. The mean number of patients who were newly started anti-hypertensive treatment during the COVID-19 season was significantly decreased as compared to the pre-COVID-19 period. Therefore the Ministry of Health Ethiopia (MOH) should update and prepare convenient care and follow-up such as remote chronic illness management methods during the ongoing COVID-19 pandemic in Ethiopia.